Strengthening the effectiveness of community health system: Assessing the factors that enhance or constrain the delivery of health services within communities in Nigeria - Okechukwu Ozor; Enyi Etiaba; Obinna Onwujekwe (BMC, 2024)
Abstract Introduction Sub-optimal community health service delivery (CHSD) has been a challenge constraining community health systems (CHS) globally, especially in developing countries such as Nigeria. This paper examined the key factors that either enhance or constrain CHSD in Nigeria at the individual, community/facility and governmental levels while recommending evidence-based solutions for sustaining and improving CHSD within the framework of CHS. Methods Data were collected through a qualitative study undertaken in three states (Anambra, Akwa-Ibom and Kano) in Nigeria. Respondents were formal/informal health providers, community leaders and representatives of civil society organizations all purposively sampled. There were 90 in-depth interviews and 12 focus group discussions, which were audio-recorded, transcribed verbatim and analysed thematically using codes to identify key themes. Results Factors constraining community health service delivery at the individual level were poor health-seeking behaviour, preference for quacks and male dominance of service delivery; at the community/facility level were superstitious/cultural beliefs and poor attitude of facility workers; at the governmental level were inadequate financial support, embezzlement of funds and inadequate social amenities. Conversely, the enabling factors at the individual level were community members' participation and the compassionate attitude of informal providers. At the community and facility levels, the factors that enhanced service delivery were synergy between formal and informal providers and support from community-based organizations and structures. At the governmental level, the enhancing factors were the government's support of community-based formal/informal providers and a clear line of communication. Conclusions Community health service delivery through a functional community-health system can improve overall health systems strengthening and lead to improved community health. Policy-makers should integrate community health service delivery in all program implementation and ultimately work with the community health system as a veritable platform for effective community health service delivery.